The Role of the Family Environment in the Social and Emotional Development of Early Childhood - Dwi Septiani; Suryadi (STIT Attaqwa, 2025)
The family plays an important role in shaping the character and social emotional development of children from an early age. A healthy family environment is the main foundation for children to learn to recognize, understand, and manage emotions and build positive social relationships. This study aims to systematically examine how the family contributes to the social emotional development of early childhood using a literature study approach. Data were obtained through searching various accredited national journals and relevant reference books from the last five years. The results of the study indicate that warm and consistent parenting patterns, open communication in the family, parental involvement in children's activities, and a harmonious household atmosphere are key factors in supporting children's social emotional growth. These findings are supported by various theories of child development, such as ecological theory and ecological development theory. In conclusion, the quality of relationships within the family greatly determines the success of children in building self-control, empathy, and other social skills. The practical implications of this study emphasize the importance of strengthening the role of the family as the main partner in early childhood education.